School Well-Being in Secondary School Students and its Conditioning Factors: A Systematic Review - Sturiale, Giusy; Espino-Díaz, Luis (Journal of Education Culture and Society, 2024)
Thesis. This systematic review article argues that school well-being is closely linked to various factors, such as academic performance, interpersonal relationships, and self-concept. It posits that promoting school well-being can significantly enhance academic motivation, reduce absenteeism, and foster a more positive learning environment.Concept. School well-being is intricately linked to various factors including academic performance, interpersonal relationships, and self-concept. This study critically evaluates these factors, organising and assessing previous research to inform future studies and pedagogical strategies.Results and conclusion. The review reveals that school well-being is significantly connected to academic performance, quality of interpersonal relationships, and self-concept. Additionally, factors such as anxiety are identified as major contributors to student distress, impacting their overall school well-being and academic outcomes. The findings suggest that promoting school well-being can effectively enhance academic motivation, reduce absenteeism, and foster a more positive learning environment. Promoting school well-being emerges as a key strategy to optimise the educational experience and academic outcomes. The study highlights the importance of tailored pedagogical approaches that address individual differences and foster a supportive and inclusive classroom environment. Integrating socio-emotional learning and continuous monitoring of student well-being are recommended for sustainable educational success.Originality. This article provides a novel synthesis of existing research on school well-being, linking it to academic performance, interpersonal relationships, and self-concept. It offers practical pedagogical guidelines based on a comprehensive literature review, highlighting the importance of socio-emotional learning and continuous monitoring of student well-being to enhance educational outcomes.